Study and implementation of load monitoring on an 11 kV underground cable distribution network - Hampton, Brent Gary (Department of Electrical Engineering, 2016)
Operating and Planning staff of an electricitY supply utility have expressed the opinion that a load monitoring system needed to be installed at protected substations forming part of an 11 kV underground cable reticulation network. Load information was currently only available from feeders connected to the 132/11 kV stepdown substations which provide infeeds to the system. The staff felt that the availability of feeder load information from the protected substation level of the 11 kV ring network would assist in more efficient system planning and more accurate system operation. This request for additional load data constituted the main motivation for the project described in this report. The two main objectives of the project can thus be stated as follows: (i) To prove conclusively that there were benefits to be derived from implementing load monitoring at protected susbstations on the 11 kV reticulation network. (ii) To implement a suitable load monitoring system if the study resulting from (i) proved this was necessary.